On diagnostics of annular-shape radio-frequency plasma jet operating in argon in atmospheric conditions. (19th March 2020) - Sremački, Ivana; Jurov, Andrea; Modic, Martina; Cvelbar, Uroš; Wang, Lei; Leys, Christophe; Nikiforov, Anton
Abstract: One of the driving forces behind the development of cold plasma sources at atmospheric pressure is their application in the biomedical field. In this respect, radio-frequency (RF) plasma jets are of particular importance due to their possible safe operation on humans and the generation of the high amount of reactive species. For this reason, we designed an RF plasma jet in co-axial geometry with the possibility of aerosol introduction, where its characteristics were evaluated by electrical diagnostics, optical emission and laser scattering spectroscopy. The RF plasma jet operation and stability of diffuse mode were analysed based on energy balance. It was observed that α -mode diffuse discharge characterised by an effluent length up to 5 mm was sustained at a power density below 30 W cm −3 . The gas and rotational temperature were determined by means of spectroscopy methods and compared with the results of direct laser scattering. It was established that the gas temperature obtained from N2 emission of transition C 3 Пu  → B 3 Пg (0, 2) is highly overestimated whereas the gas temperature estimated from OH transition A 2 Σ+ → X 2 Пi (0, 0) gave a reasonable agreement with both Rayleigh and Raman spectroscopy. Based on the Rayleigh scattering method, uniform gas temperature distribution in the discharge effluent was found at a power below 15 W with the average temperature below 340 ± 15 K. The low gas temperature of argon plasma jets would allow use of this source in temperature-sensitive material applications including skin treatments.